2011
DOI: 10.17305/bjbms.2011.2569
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl ester transfer protein, low density lipoprotein particle size and intima media thickness in patients with coronary heart disease

Abstract: Cholesteryl ester transfer protein (CETP) plays a key role in reverse cholesterol transport and high density lipoprotein (HDL) metabolism. Predominance of small, dense LDL particles is associated with an increased risk of atherosclerosis and coronary heart disease (CHD). Th e aim of the study was to determine the potential relationship between the CETP concentration and low density lipoprotein (LDL) particle size and their association with intima media thickness (IMT) in patients with CHD. Lipid parameters, CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…22 Small LDL size is also associated with thicker cIMT in middle age subjects with metabolic syndrome 23 and in patients with coronary artery disease. 24, 25 In subjects with T2DM, small LDL was more highly associated with cIMT than LDL-C 26 retaining significance even after adjustment for other risk factors. 27 The importance of LDL particle number and size are not entirely clear for subjects with T1DM as the DCCT/EDIC study found stronger relationship between cIMT and LDL-C than LDL-P or LDL-S. 28 Similar to our data, however, they found all lipid parameters related more strongly to the internal than the common carotid artery.…”
Section: Discussionmentioning
confidence: 96%
“…22 Small LDL size is also associated with thicker cIMT in middle age subjects with metabolic syndrome 23 and in patients with coronary artery disease. 24, 25 In subjects with T2DM, small LDL was more highly associated with cIMT than LDL-C 26 retaining significance even after adjustment for other risk factors. 27 The importance of LDL particle number and size are not entirely clear for subjects with T1DM as the DCCT/EDIC study found stronger relationship between cIMT and LDL-C than LDL-P or LDL-S. 28 Similar to our data, however, they found all lipid parameters related more strongly to the internal than the common carotid artery.…”
Section: Discussionmentioning
confidence: 96%
“…Our present results further confirmed that the plasma preβ1-HDL levels elevated with high CETP mass in patients with CAD. As we all known, CETP plays an important role in the transfer and exchange of CE and TG among lipoproteins, so that it affects lipid composition, concentration, particle size and function of lipoprotein [12]. In addition, it is now accepted that virtually all of the efflux mediated by the ABCA1 transporter goes to preβ1-HDL, which contains only one molecular species of protein, apoA-I.…”
Section: Discussionmentioning
confidence: 99%
“…It relates to particle size, lipid composition and function of lipoprotein [12]. CETP also plays a key role in reverse cholesterol transport (RCT) and development of atherosclerosis [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…We divided the table according to investigations showing an increase or a decrease in CETP levels in plasma. We observed that, in general, the variation in CETP had the tendency to bring about consistent changes in the plasma lipoprotein profile, namely high CETP tends to produce a pro‐atherogenic lipoprotein profile in 14 of 16 investigations . However, the degree of atherosclerosis worsened in eight of them only , diminished in four and was not modified in 3 .…”
Section: Resultsmentioning
confidence: 77%